Energy-Efficient Parametric Optimization of Al7178/TiB2/SiO2 Hybrid Nanocomposites through SN ratio and ANOVA method - Seetharaman Suresh; Geetha M.; Pushparaj J. Paulmar; Devi P. Renuka; Pant Ruby; Singh Maninder (E3S Web of Conferences)
This work focused on the energy-efficient fabrication of Al7178 based hybrid nanocomposites reinforced with TiB2 & SiO2 by using the stir-casting technique. The investigation aimed to optimize process factors including stirring speed, stirring time, reinforcement weight percentage, and preheat temperature, to improve the tensile strength of the Al7178/TiB2/SiO2 hybrid composite. The Taguchi method and ANOVA were employed to analyze the influence of these parameters on tensile strength. SN ratio analysis helped to identify the optimal parameter settings. Results confirmed that preheat temperature, stir time, and reinforcement weight percentage had a statistically significant impact on tensile strength. Optimal conditions were identified as 800 rpm, 740°C of preheat temperature, 8 wt% of reinforcement, and 9 minutes of stir time, lead to a substantial improvement in tensile strength. These conclusions contributed to the development of energy-efficient and high-performance Al-based hybrid composites.